Typical and extreme weather datasets for studying the resilience of buildings to climate change and heatwaves - Anaïs Machard; Agnese Salvati; Mamak P. Tootkaboni; Abhishek Gaur; Jiwei Zou; Liangzhu Leon Wang; Fuad Baba; Hua Ge; Facundo Bre; Emmanuel Bozonnet; Vincenzo Corrado; Xuan Luo; et al. (Scientific Data)
Abstract We present unprecedented datasets of current and future projected weather files for building simulations in 15 major cities distributed across 10 climate zones worldwide. The datasets include ambient air temperature, relative humidity, atmospheric pressure, direct and diffuse solar irradiance, and wind speed at hourly resolution, which are essential climate elements needed to undertake building simulations. The datasets contain typical and extreme weather years in the EnergyPlus weather file (EPW) format and multiyear projections in comma-separated value (CSV) format for three periods: historical (2001–2020), future mid-term (2041–2060), and future long-term (2081–2100). The datasets were generated from projections of one regional climate model, which were bias-corrected using multiyear observational data for each city. The methodology used makes the datasets among the first to incorporate complex changes in the future climate for the frequency, duration, and magnitude of extreme temperatures. These datasets, created within the IEA EBC Annex 80 “Resilient Cooling for Buildings”, are ready to be used for different types of building adaptation and resilience studies to climate change and heatwaves.